A method for preparing aluminum-silicon-based ceramic core by light-curing additive manufacturing-hot pressing composite molding
Through light-curing additive manufacturing and hot-pressure injection composite molding technology, an aluminum-silicon-based ceramic core was prepared, which solved the problem of fracture of the ceramic core during wax pressing and pouring, improved the production qualification rate of hollow turbine blades, and Achieved good yield and high impact resistance.
Patent Information
- Application Number
- CN202411492722.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-24
- Publication Date
- 2025-01-21
- Estimated Expiration
- 2044-10-24
Smart Images

Figure CN118989251B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of precision casting technology, and more specifically, to an aluminum-silicon-based ceramic core and a photocuring additive manufacturing-hot pressing composite molding preparation method thereof. Background Art
[0002] At present, the precision casting of gas turbine blades for aircraft engines mostly adopts the method of investment casting. With the continuous increase in the demand for blade temperature bearing capacity, the structure of turbine blades has developed from a simple solid structure to a complex air-cooled multi-cavity hollow structure. The ceramic core is an important adapter for forming the inner cavity of the hollow blade. The complexity of the inner cavity structure of the blade leads to a multi-cavity and multi-layer structure of the ceramic core, which is difficult to prepare. In particular, there are a large number of fine structures (cross-sectional size <3mm) on the ceramic core, such as exhaust edges, connecting columns, connecting necks, etc. Due to their small size, the fine structure can withstand a small bending load. In the wax pressing and pouring process of the ceramic core, it is the first to break due to thermal and mechanical stress, which reduces the qualified rate of the turbine blade.
[0003] At the same time, the ceramic core for directional or single crystal turbine blades needs to have good yieldability, that is, when the molten metal just solidifies, the high temperature strength of the ceramic core and the casting should be roughly equivalent to avoid secondary crystallization of high temperature alloys. Silicon oxide-based ceramic cores are widely used due to their good yieldability, removability and thermal shock resistance. Silicon-based ceramic cores use SiO2 as the main material and quartz as the main crystal phase. The room temperature bending strength is about 10~25MPa, and the high temperature strength at 1500℃ is 20~40MPa. However, it is difficult for silicon-based ceramic cores to ensure the impact resistance of fine structures. Therefore, it is urgent to develop a ceramic core with good yieldability in the main part and high impact resistance in the fine structure.
[0004] At present, the prior art generally prepares high-strength refractory metal core pieces by laser cutting, machining, welding and other methods, and then connects the refractory metal core pieces with ceramic pieces by mechanical interlocking or chemical bonding to form a composite ceramic core of ceramic-refractory metal core. However, the above prior art has the following disadvantages: during the roasting and pouring process, the refractory metal core pieces are at risk of oxidation and reaction with high-temperature alloys; the composite ceramic cores need to be sintered non-oxidatively, which increases the difficulty of the preparation process; the refractory metal cores need to be removed by acid solution, which increases the possibility of corrosion damage to high-temperature alloy castings.
[0005] In addition, other existing technologies also pre-place quartz glass rods in the ceramic core mold based on hot pressing technology to replace the silicon-based ceramic round rods that are pressed into one piece, forming a silicon-based ceramic core with added quartz glass rods, thereby effectively solving the problem of core fracture caused by insufficient strength of the ceramic round rods. However, this technology only involves simple cylindrical quartz glass rods, and for quartz glass rods with complex and fine special-shaped structures, the technology is limited in its promotion and application due to the difficulty of preparation and low dimensional accuracy; and this technology does not discuss in detail the interface separation problem caused by different thermal expansion and contraction rates between the quartz glass rod and the silicon-based ceramic core, which leads to defects at the junction of the quartz glass rod and the silicon-based ceramic core during roasting and casting in actual applications. Summary of the invention
[0006] In view of this, the purpose of the present invention is to provide a light-curing additive manufacturing-hot pressing composite molding preparation method for an aluminum-silicon based ceramic core, which can prepare a ceramic core with good yielding property in the main part and high impact resistance in the fine structure, and solve the core breakage problem existing in the wax pressing and pouring links of the existing ceramic core, thereby improving the production qualification rate of hollow turbine blades.
[0007] The present invention provides a method for preparing an aluminum-silicon-based ceramic core by light-curing additive manufacturing-hot pressing composite molding, comprising the following steps:
[0008] Step S01: according to the structural model of the ceramic core, the ceramic core is divided into a photo-curing additive manufacturing molding part 1 and a hot injection molding part 2;
[0009] Step S02: designing a digital model of the photo-curing additive manufacturing molding part 1, including a molding end 1-1 and a bonding end 1-2;
[0010] Step S03: Printing, sintering and trimming are performed using a photo-curing additive manufacturing method to prepare a photo-curing additive manufacturing molding part 1;
[0011] Step S04: Design a ceramic core mold for preparing the hot injection molding part 2. The mold should be designed with a limit slot for placing the light-curing additive manufacturing molding part 1;
[0012] Step S05: placing the photo-curing additive manufacturing molding part 1 into the limiting slot of the ceramic core mold, preparing the hot-pressing molding part 2 by hot-pressing method, and forming a complete ceramic core green body in which the hot-pressing molding part 2 tightly covers the joint end 1-2;
[0013] Step S06: visually inspecting to confirm that the photo-curing additive manufacturing molding part 1 and the green hot-pressing injection molding part 2 have no defects, and that there are no defects at the junction of the two;
[0014] Step S07: Sintering to form a sintered ceramic core, cooling it to room temperature and then taking it out of the furnace;
[0015] Step S08: Visual inspection to confirm that the ceramic core as a whole has no defects, that is, the aluminum-silicon based ceramic core is prepared.
[0016] Preferably, the photocuring additive manufacturing molding part 1 in step S01 is a fine structure with tiny size on the ceramic core, which is made of high-strength aluminum-based ceramic material; the hot pressing molding part 2 is the main part of the ceramic core, which is made of silicon-based ceramic material.
[0017] Preferably, in step S02 , the molding end 1 - 1 participates in forming the outer structure of the ceramic core, and the combining end 1 - 2 is used to combine with the hot injection molding part 2 .
[0018] Preferably, the surface of the bonding end 1 - 2 has a concave-convex micro-texture structure, and the depth of the texture is greater than the gap width caused by the mismatch between the thermal expansion coefficient and the sintering shrinkage coefficient of the aluminum-based ceramic material and the silicon-based ceramic material.
[0019] Preferably, the ceramic slurry of the aluminum-based ceramic part in step S03 comprises:
[0020] Ceramic powder 55~85wt%, photosensitive resin 10~45wt%, dispersant 1~5wt%, additive 0.1~3wt%.
[0021] Preferably, the ceramic powder is composed of 95-99.9wt% of aluminum oxide powder, 0.1-5wt% of silicon oxide powder, and 0.1-3wt% of silicon nitride whiskers; the aluminum oxide powder is composed of powders with particle sizes of 0.1-0.5μm, 1-2μm and 3-5μm in a mass ratio of (1.5-2.5): (6-8): 1; the silicon oxide powder is a spherical powder with a particle size of 0.3-0.8μm; the photosensitive resin is composed of 0.4-1wt% of an external TPO photoinitiator, 60-90wt% of a HDDA resin, 3-15wt% of a TMPTA resin, 3-15wt% of a PPTTA resin, and 3-15wt% of a PEG400DA resin; the dispersant is DISPERBYK-110; and the additives include one or more of polyethylene fibers, multi-walled carbon nanotubes, and starch.
[0022] Preferably, the open porosity of the aluminum-based ceramic part in step S03 is 5-30%, the three-point bending strength at room temperature is not less than 300 MPa, and it can be removed by soaking in high temperature and high pressure KOH alkali solution.
[0023] Preferably, the ceramic core mold used for hot-pressing molding part 2 in step S04 should be designed with a limit slot for placing the photocuring additive manufacturing molding part 1, and a filling space for silicon-based ceramic slurry should be left around the joint end 1-2 so that the thickness of the silicon-based ceramic slurry is greater than 0.5 mm.
[0024] Preferably, the hot pressing method in step S05 is: using a core pressing machine to inject molten silicon-based ceramic slurry into a ceramic core mold under certain injection parameters, and after a certain holding time, the silicon-based ceramic slurry is cooled and solidified to form a complete ceramic core green body in which the hot pressing molding part 2 covers the light-curing additive manufacturing molding part 1;
[0025] The injection pressure is 4.0-7.8 MPa, the injection time is 3-8 s, the holding time is 20-50 s, the mold closing pressure is 4.0-8.0 MPa, the mold temperature is 30-45° C., and the slurry temperature is 60-110° C.
[0026] Preferably, the silicon-based ceramic component in step S07 has an open porosity of 20-40%, a three-point bending strength at room temperature of 10-20 MPa, and a solubility in 37% KOH boiling alkali solution of 0.08-0.15 g / min.
[0027] Compared with the prior art, the preparation method provided by the present invention adopts specific process steps to achieve better overall interaction. The prepared aluminum-silicon based ceramic core is a light-curing additive manufacturing-hot pressing composite formed aluminum-silicon ceramic core. The main part has good yieldability and the fine structure has high impact resistance. The ceramic core solves the core breakage problem of the ceramic core during the wax pressing and pouring links and improves the production qualification rate of hollow turbine blades. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Figure 1 A flow chart of the preparation method provided by the present invention;
[0029] Figure 2 This is a schematic diagram of a special-shaped connecting column of a ceramic core head manufactured by photocuring additive manufacturing according to Example 1 of the present invention, and the surface of the molding end has a serrated texture;
[0030] Figure 3 This is a schematic diagram of a special-shaped connecting column of a ceramic core head manufactured by photocuring additive manufacturing according to Example 2 of the present invention, and the surface of the molding end has a threaded texture;
[0031] Figure 4 This is a schematic diagram of a special-shaped connecting column of a ceramic core head manufactured by photocuring additive manufacturing according to Example 3 of the present invention, and the surface of the molding end has a dot matrix pit-shaped texture;
[0032] Figure 5It is a schematic diagram of a cylindrical connecting column of a ceramic core head manufactured by photocuring additive manufacturing according to Example 4 of the present invention;
[0033] Figure 6 It is a schematic diagram of a photo-curing additive manufacturing ceramic core connection neck according to Example 5 of the present invention;
[0034] In the figure: 1 photo-curing additive manufacturing molding part; 2 hot injection molding part; 1-1 molding end; 1-2 bonding end. DETAILED DESCRIPTION
[0035] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0036] The present invention provides a method for preparing an aluminum-silicon-based ceramic core by light-curing additive manufacturing-hot pressing composite molding, comprising the following steps:
[0037] Step S01: according to the structural model of the ceramic core, the ceramic core is divided into a photo-curing additive manufacturing molding part 1 and a hot injection molding part 2;
[0038] Step S02: designing a digital model of the photo-curing additive manufacturing molding part 1, including a molding end 1-1 and a bonding end 1-2;
[0039] Step S03: Printing, sintering and trimming are performed using a photocuring additive manufacturing method to prepare a photocuring additive manufacturing molding part 1;
[0040] Step S04: Design a ceramic core mold for preparing the hot injection molding part 2. The mold should be designed with a limit slot for placing the light-curing additive manufacturing molding part 1;
[0041] Step S05: placing the photo-curing additive manufacturing molding part 1 into the limiting slot of the ceramic core mold, preparing the hot-pressing molding part 2 by hot-pressing method, and forming a complete ceramic core green body in which the hot-pressing molding part 2 tightly covers the joint end 1-2;
[0042] Step S06: visually inspecting to confirm that the photo-curing additive manufacturing molding part 1 and the green hot-pressing injection molding part 2 have no defects, and that there are no defects at the junction of the two;
[0043] Step S07: Sintering to form a sintered ceramic core, cooling it to room temperature and then taking it out of the furnace;
[0044] Step S08: Visual inspection to confirm that the ceramic core as a whole has no defects, that is, the aluminum-silicon based ceramic core is prepared.
[0045] See also Figure 1 , Figure 1 The present invention provides a flow chart of the preparation method.
[0046] The present invention first performs step S01 to divide the ceramic core structure: according to the structural model of the ceramic core, the ceramic core is divided into a photo-curing additive manufacturing molding part 1 and a hot injection molding part 2.
[0047] In the present invention, the photocuring additive manufacturing molding part 1 in step S01 is preferably a fine structure with tiny size on a ceramic core, preferably made of high-strength aluminum-based ceramic material; the hot pressing molding part 2 is preferably the main part of the ceramic core, preferably made of silicon-based ceramic material.
[0048] Then, step S02: designing a digital model of the photo-curing additive manufacturing molding part 1, including two parts: the molding end 1-1 and the bonding end 1-2.
[0049] In the present invention, the molding end 1 - 1 in step S02 is preferably involved in forming the outer structure of the ceramic core, and the combining end 1 - 2 is preferably used to combine with the hot injection molding part 2 .
[0050] In the present invention, the step S02 preferably further comprises: designing the structure of the forming end 1-1 according to the inner cavity structure of the casting; scaling the size of the forming end 1-1 based on the inner cavity size requirements of the casting and the sintering shrinkage of the aluminum-based ceramic material. In the present invention, the sintering shrinkage of the aluminum-based ceramic material includes the shrinkage aa1 of the sintering of the aluminum-based ceramic green body, the shrinkage aa2 of the sintering stage of the silicon-based ceramic green body, and the shrinkage aa3 of the casting process.
[0051] In the present invention, the step S02 preferably further includes: designing the structure of the joint end 1 - 2 according to the structure of the joint of the photocuring additive manufacturing molding part 1 (ceramic core part) and the hot injection molding part 2 .
[0052] In the present invention, the surface of the bonding end 1-2 should preferably be designed with a concave-convex micro-texture structure, such as a thread or a serration, and the depth of the texture is preferably greater than the gap width (denoted as: d) caused by the difference in thermal expansion rate and sintering shrinkage rate between the aluminum-based ceramic material and the silicon-based ceramic material, so as to avoid separation of the bonding interface between the photocuring additive manufacturing molding part 1 and the hot pressing molding part 2. In the present invention, the gap width d can be estimated according to the following method: Since the strength of the aluminum-based ceramic part is much greater than the strength of the silicon-based ceramic material, it can be assumed that the deformation of the aluminum-based ceramic part can cause the deformation of the silicon-based ceramic material, and vice versa; in the sintering process of the silicon-based ceramic green body (step S07), on the one hand, the maximum thermal expansion rate of the aluminum-based ceramic material is ab2, and the sintering shrinkage rate is aa2; on the other hand, the silicon-based ceramic core green body is degreased and sintered to form a sintered state, and the sintering shrinkage rate is sa1; in the high temperature bonding process (step S07), the maximum thermal expansion rate of the aluminum-based ceramic material is ab2, and the sintering shrinkage rate is aa2. On the other hand, the silicon-based ceramic core green body is degreased and sintered to form a sintered state, and the sintering shrinkage rate is sa1. During the alloy pouring process, the maximum thermal expansion coefficient of the aluminum-based ceramic material is ab3, the sintering shrinkage rate is aa3, the sintering shrinkage rate of the silicon-based ceramic core is sa2, and the cross-sectional characteristic dimension of the bonding end 1-2 is x. After two thermal processes of sintering the silicon-based ceramic green body and pouring the high-temperature alloy, the gap width d can be estimated to be equal to x*{[(1+ab2)*(1+ab3)-1]+[1-(1-aa2)*(1-aa3)]+[1-(1-sa1)*(1-sa2)]}.
[0053] Then, step S03: according to the digital model of the photocuring additive manufacturing molding part 1 designed in step S02, a photocuring additive manufacturing method is used to print, sinter and trim, so as to prepare an aluminum-based ceramic part, namely, the photocuring additive manufacturing molding part 1.
[0054] In the present invention, the ceramic slurry of the aluminum-based ceramic part in step S03 preferably includes:
[0055] Ceramic powder 55~85wt%, photosensitive resin 10~45wt%, dispersant 1~5wt%, additive 0.1~3wt%;
[0056] More preferably, it is composed of the following components:
[0057] Ceramic powder 55~85wt%, photosensitive resin 10~45wt%, dispersant 1~5wt%, additive 0.1~3wt%;
[0058] In the present invention, the ceramic powder is composed of 95-99.9wt% alumina powder, 0.1-5wt% silicon oxide powder, and 0.1-3wt% silicon nitride whisker; the alumina powder is composed of powders with particle sizes of 0.1-0.5μm, 1-2μm, and 3-5μm in a mass ratio of (1.5-2.5): (6-8): 1, and more preferably, the alumina powder is composed of powders with particle sizes of 0.2-0.5μm, 1-2μm, and 3-5μm in a mass ratio of 2:7:1; The silicon powder is a spherical powder with a particle size of 0.3-0.8 μm; the photosensitive resin is composed of 0.4-1 wt% of an external TPO photoinitiator, 60-90 wt% of a HDDA resin, 3-15 wt% of a TMPTA resin, 3-15 wt% of a PPTTA resin, and 3-15 wt% of a PEG400DA resin; the dispersant is DISPERBYK-110; the additive preferably includes one or more of polyethylene fiber, multi-walled carbon nanotubes, and starch. The present invention has no particular restrictions on the sources of the above raw materials, and commercially available products known to those skilled in the art can be used.
[0059] In the present invention, the fine powder in the ceramic powder increases the sintering degree and ensures the high strength of the aluminum-based ceramic parts; the polyethylene fibers and multi-walled carbon nanotubes are used to increase the strength and toughness of the 3D printed ceramic parts green body, which is convenient for subsequent processing; the starch forms a certain porosity in the aluminum-based ceramic material, which is convenient for the subsequent core removal.
[0060] In the present invention, the printed aluminum-based ceramic part is preferably sintered at a final firing temperature of 1400-1700°C.
[0061] In the present invention, the open porosity of the aluminum-based ceramic part in step S03 is preferably 5-30%, and the three-point bending strength at room temperature is preferably not less than 300 MPa, which can be removed by soaking in high temperature and high pressure KOH alkali solution.
[0062] Further, step S04: designing a ceramic core mold according to the ceramic core structure for preparing the hot injection molding part 2 , and the mold should be designed with a limiting slot for placing the photo-curing additive manufacturing molding part 1 .
[0063] In the present invention, the ceramic core mold in step S04 is preferably designed with a limit slot for placing the photocuring additive manufacturing molding part 1. In the present invention, the limit slot is preferably tightly fitted with the molding end 1-1 of the photocuring additive manufacturing molding part, the connecting end 1-2 should be suspended in the mold, and the straight-line distance between the connecting end 1-2 and the inner wall of the ceramic core mold cavity is preferably not less than 0.5 mm to ensure that the silicon-based ceramic slurry covers the connecting end 1-2 well.
[0064] Then, step S05: place the photocuring additive manufacturing molding part 1 into the limiting slot of the ceramic core mold, prepare the hot injection molding part 2 by hot injection, and use a core pressing machine to form a complete ceramic core green body with the hot injection molding part 2 covering the joint end 1-2.
[0065] In the present invention, the hot pressing method described in step S05 is preferably: using a core pressing machine to inject molten silicon-based ceramic slurry into a ceramic core mold under certain injection parameters, and after a certain holding time, the silicon-based ceramic slurry is cooled and solidified to form a complete ceramic core green body in which the hot pressing molding part 2 covers the photocuring additive manufacturing molding part 1.
[0066] In the present invention, the injection pressure is preferably 4.0~7.8MPa, the injection time is preferably 3~8s, more preferably 5~8s, the holding time is preferably 20~50s, the mold closing pressure is preferably 4.0~8.0MPa, the mold temperature is preferably 30~45°C, more preferably 35~45°C, and the slurry temperature is preferably 60~110°C, more preferably 90~110°C.
[0067] In the present invention, the silicon-based ceramic slurry preferably comprises:
[0068] Ceramic powder 80~90wt%, plasticizer 10~20wt%;
[0069] More preferably:
[0070] Ceramic powder 80~90wt% and plasticizer 10~20wt%.
[0071] In the present invention, the ceramic powder is preferably composed of 80-98wt% of quartz glass powder and 2-20wt% of mineralizer; the plasticizer is preferably composed of 80-95wt% of paraffin wax, 1-10wt% of polyethylene, and 0.1-10wt% of organic additives. The present invention has no particular restrictions on the sources of the above raw materials, and commercially available products known to those skilled in the art can be used.
[0072] Afterwards, step S06: visual inspection is performed to confirm that the photo-curing additive manufacturing molding part 1 and the green hot-pressing molding part 2 have no defects, and that there are no defects at the junction of the two.
[0073] Then, step S07: sintering to form a sintered ceramic core, which is then taken out of the furnace after cooling to room temperature.
[0074] The present invention preferably inserts the above-mentioned ceramic core green body into the kaolin filler of the calcination pot so that the filler completely covers the ceramic core, and then puts the calcination pot into a roasting furnace. After the final firing temperature is 1100~1400℃, the silicon-based ceramic green body is transformed into a sintered state and is taken out of the furnace after cooling to room temperature.
[0075] In the present invention, the performance of the silicon-based sintered ceramic part is preferably: open porosity is 20-40%, three-point bending strength at room temperature is 10-20 MPa, and solubility in 37% KOH boiling alkali solution is 0.08-0.15 g / min.
[0076] Finally, step S08: visual inspection to confirm that the ceramic core as a whole has no defects, that is, the aluminum-silicon based ceramic core is prepared.
[0077] In the present invention, the visual inspection of step S06 and the visual inspection of step S08 preferably require that the position of the photocuring additive manufacturing molding part 1 (aluminum-based ceramic part) is correct, the bonding end 1-2 has no leakage, the silicon-based ceramic material covering the outer layer of the bonding end 1-2 has no cracks, and the bonding interface between the photocuring additive manufacturing molding part 1 and the hot compression molding part 2 has no gap.
[0078] The preparation method provided by the present invention uses a photocuring additive manufacturing method to prepare a high-strength aluminum-based ceramic fine special-shaped structure, and uses a hot pressing method to prepare a silicon-based ceramic core main structure, so that the ceramic core has both impact resistance, solubility and yieldability, and has the advantages of a short preparation cycle, high dimensional accuracy, and convenient structural adjustment. It can reduce the risk of the ceramic core being scrapped due to breakage and effectively improve the product qualification rate of hollow turbine blades. Compared with the prior art, the preparation method provided by the present invention adopts specific process steps to achieve better overall interaction. The prepared aluminum-silicon-based ceramic core is a photocuring additive manufacturing-hot pressing composite aluminum-silicon ceramic core. The main part has good yieldability and the fine structure has a high impact resistance. The ceramic core solves the problem of core breakage of the ceramic core in the wax pressing and pouring links and improves the production qualification rate of hollow turbine blades.
[0079] In order to further illustrate the present invention, the following examples are provided for detailed description. Example 1
[0080] A ceramic core for a high-temperature alloy turbine blade is selected as the verification object, as shown in the figure Figure 2 As shown, the photo-curing additive manufacturing molding part 1 is a connecting column of the ceramic core head, which is used to form a process hole at the cover plate of the working blade; the hot injection molding part 2 is the remaining ceramic core part.
[0081] Design a digital model of the photo-curing additive manufacturing molding part 1, including the molding end 1-1 and the connecting end 1-2. Based on the inner cavity structure and size requirements of the casting, the structure of the molding end 1-1 is designed and the size is scaled according to the sintering shrinkage rate of the aluminum-based ceramic material. Specifically: the inner cavity of the casting requires the connecting column to be a special-shaped column with a runway-shaped cross-section, with a length of 2.00mm in the x-direction and 1.00mm in the y-direction; the shrinkage rate of the sintering of the aluminum-based ceramic material green body is aa1=0.20%, the shrinkage rate in the silicon-based ceramic green body sintering process is aa2=0.03%, and the shrinkage rate in the casting process is aa3=0.05%; in order to prevent the connecting end 1-2 from being exposed, the length of the molding end 1-1 is appropriately lengthened, and the structure of the molding end 1-1 of the aluminum-based ceramic connecting column is: a special-shaped column with a runway-shaped cross-section, with a size of 2.01mm in the x-direction, 1.00mm in the y-direction, and 5.00mm in the z-direction, as shown in the schematic diagram. Figure 2 shown.
[0082] Design the structure of the binding end 1-2. Specifically: Figure 2 As shown, the upper end of the connecting column is the forming end 1-1, and the lower end is the connecting end 1-2. The silicon-based ceramic part combined with the connecting column is a thin-walled structure, with a dimension of 1.70mm in the y direction, and the dimensions in the x and z directions are much larger than the dimensions of the connecting column. In order to ensure that the thickness of the silicon-based ceramic slurry coated around the connecting end 1-2 is greater than 0.50mm, the structure of the connecting end 1-2 of the aluminum-based ceramic connecting column is set as: a special-shaped column with a runway-shaped cross-section, with a dimension of 2.01mm in the x direction, 0.70mm in the y direction, and 4.00mm in the z direction, as shown in the schematic diagram Figure 2 shown.
[0083] A concave-convex micro-texture structure is designed on the surface of the joint end 1-2, and the depth of the texture is greater than the gap width d caused by the difference in thermal expansion rate and sintering shrinkage rate between the aluminum-based ceramic material and the silicon-based ceramic material. The gap width d is estimated as follows: in the sintering process of the silicon-based ceramic green body (step S07), the final sintering temperature is 1300°C, the maximum thermal expansion rate of the aluminum-based ceramic material is ab2=0.85%, the sintering shrinkage rate is aa2=0.03%, and the sintering shrinkage rate of the silicon-based ceramic core green body is sa1=0.5%; in the high-temperature alloy pouring process, the highest temperature is 1500°C, the maximum thermal expansion rate of the aluminum-based ceramic material is ab3=1.15%, the sintering shrinkage rate is aa3=0.05%, and the sintering shrinkage rate of the silicon-based ceramic core is sa2=0.8%. The cross-sectional characteristic size of the joint end 1-2 is 2.01mm. After two thermal processes of sintering the silicon-based ceramic green body and pouring the high-temperature alloy, the gap width d can be estimated to be equal to 0.07mm. Therefore, the concave-convex micro-texture structure designed on the surface of the bonding end 1-2 is specifically set to: a sawtooth structure with a texture depth of 0.1 mm, as shown in the schematic diagram Figure 2 shown.
[0084] According to the digital model of the photocuring additive manufacturing forming part 1 designed above, the photocuring additive manufacturing method is used for printing, sintering and trimming to obtain the aluminum-based ceramic part of the photocuring additive manufacturing forming part 1. The aluminum-based ceramic slurry used in the photocuring additive manufacturing method is prepared from the following raw materials:
[0085] Ceramic powder 76wt%, photosensitive resin 20wt%, dispersant 2wt%, additive 2wt. Ceramic powder is prepared by proportioning 98wt% of aluminum oxide powder, 1.3wt% of silicon oxide powder, and 0.7wt% of silicon nitride whisker. Aluminum oxide powder is prepared by powders with particle sizes of 0.1~0.5μm, 1~2μm, and 3~5μm in a ratio of 2:7:1, and the particle size of silicon oxide powder is 0.3~0.8μm. Photosensitive resin is prepared by proportioning 0.5wt% of TPO photoinitiator, 75wt% of HDDA resin, 10wt% of TMPTA resin, 10wt% of PPTTA resin, and 4.5wt% of PEG400DA resin. Dispersant is DISPERBYK-110. Additives include polyethylene fiber, multi-walled carbon nanotubes, and starch. The printed aluminum-based ceramic parts are sintered at a final firing temperature of 1600℃. The open porosity is 13~17%, the three-point flexural strength at room temperature is greater than 300MPa, and it can be removed by soaking in high temperature and high pressure KOH solution.
[0086] The ceramic core mold is designed according to the ceramic core structure and is used for hot pressing molding of the hot pressing molding part 2. The ceramic core mold is designed with a limit slot for placing the photocuring additive manufacturing molding part 1 (connecting column). The limit slot should fit tightly with the molding end 1-1 of the photocuring additive manufacturing molding part, and the joint end 1-2 should be suspended in the mold, and the straight-line distance between the joint end 1-2 and the inner wall of the ceramic core mold cavity should not be less than 0.5 mm.
[0087] The photocuring additive manufacturing molding part 1 (connecting column) is placed in the limiting groove of the ceramic core mold. Through the hot injection method, the molten silicon-based ceramic slurry is injected into the mold under certain injection parameters using a core pressing machine. After a certain holding time, the silicon-based ceramic slurry is cooled and solidified to form a complete ceramic core green body with the hot injection molding part 2 covering the photocuring additive manufacturing molding part 1 (connecting column).
[0088] Among them, the silicon-based ceramic slurry used for hot pressing molding is prepared from the following raw materials: ceramic powder 85wt%, plasticizer 15wt%; ceramic powder is prepared by quartz glass powder 90wt%, mineralizer 10wt% in proportion; plasticizer is prepared by paraffin 90wt%, polyethylene 5wt%, organic additive 5wt% in proportion. The pressing parameters of hot pressing are: injection pressure 5.0MPa, injection time 8s, holding time 30s, mold clamping pressure 5.0MPa, mold temperature 40℃, and slurry temperature 100℃.
[0089] Visual inspection confirms that the photocuring additive manufacturing part 1 (aluminum-based ceramic connecting column) and the hot pressing molding part 2 (green silicon-based ceramic core body part) have no defects. The photocuring additive manufacturing part 1 (aluminum-based ceramic connecting column) is in the correct position, the joint end 1-2 has no leakage, the green silicon-based ceramic material covering the outer layer of the joint end 1-2 has no cracks, and there is no gap between the joint interface of the aluminum-based ceramic connecting column and the core body part, then the firing process can be carried out.
[0090] Insert the ceramic core green body into the kaolin filler of the calcined pot so that the filler completely covers the ceramic core. Put the calcined pot into the roasting furnace, and after the final firing temperature is 1300℃, the silicon-based ceramic is transformed into a sintered state, and is taken out of the furnace after cooling to room temperature. The open porosity of the sintered silicon-based ceramic structure is 29~31%, the three-point bending strength at room temperature is 13~14MPa, and the solubility in 37% KOH boiling alkali solution is 0.12~0.15g / min.
[0091] Visual inspection confirms that the ceramic core has no defects as a whole, the aluminum-based ceramic connecting column is positioned correctly, there is no leakage at the joint end 1-2, there is no crack in the sintered silicon-based ceramic material covering the outer layer of the joint end 1-2, and there is no gap at the joint interface between the aluminum-based ceramic connecting column and the main part of the core, thus obtaining a finished aluminum-silicon-based ceramic core. Example 2
[0092] The verification object and process of Example 2 are the same as those of Example 1, except that the concave-convex micro-texture structure on the surface of the light-cured additive manufacturing connecting column joint end 1-2 is threaded, and the thread depth is 0.1 mm, as shown in the schematic diagram Figure 3 shown. Example 3
[0093] The verification object and process of Example 3 are the same as those of Example 1, except that the concave-convex micro-texture structure on the surface of the light-cured additive manufacturing connecting column joint end 1-2 is in the form of a dot matrix pit, and the pit depth is 0.1 mm, as shown in the schematic diagram Figure 4 shown. Example 4
[0094] A ceramic core for a high-temperature alloy turbine blade is selected as the verification object, as shown in the figure Figure 5 As shown, the photo-curing additive manufacturing molding part 1 is a connecting column of the ceramic core head, which is used to connect the ceramic core head and the blade body, and form a process hole at the cover plate of the working blade; the hot press molding part 2 is the remaining ceramic core part.
[0095] Design a digital model of the photo-curing additive manufacturing molding part 1, including a molding end 1-1 and a bonding end 1-2. Design the structure of the molding end 1-1 according to the inner cavity structure of the casting. And based on the requirements of the inner cavity size of the casting, the size of the molding end 1-1 is scaled according to the sintering shrinkage rate of the aluminum-based ceramic material. Specifically, the forming end 1-1 includes two parts. The inner cavity of the casting requires the connecting column to be a slender cylinder with a diameter of 1.00mm. The shrinkage rate of the aluminum-based ceramic material green body during sintering is aa1=0.20%, the shrinkage rate in the silicon-based ceramic green body sintering process is aa2=0.03%, and the shrinkage rate in the casting process is aa3=0.05%. Therefore, the size of the forming end 1-1 is scaled. In order to prevent the connecting end 1-2 from being exposed, the length of the forming end 1-1 is appropriately lengthened, and the structure of the aluminum-based ceramic connecting column forming end 1-1 is: two parts of slender cylinders, respectively located at the upper end and the middle part of the connecting column, with lengths of 10.00mm and 2.50mm respectively, and a diameter of 1.00mm, as shown in the schematic diagram. Figure 5 shown.
[0096] The structure of the joint end 1-2 is designed according to the structure of the joint of the photo-curing additive manufacturing molding part 1 (ceramic core part) and the hot injection molding part 2. Specifically: as shown in the figure Figure 5 As shown, the joint end 1-2 includes two parts, which are located in the middle and lower ends of the connecting column respectively. The thickness of the ceramic core head is 8.50mm. In order to ensure that the joint end 1-2 is not exposed and the thickness of the silicon-based ceramic slurry wrapped around it is greater than 0.50mm, the structure of the joint end 1-2 of the light-curing additive manufacturing connecting column is set as follows: two parts of slender cylinders, which are located in the middle and lower ends of the connecting column respectively, with lengths of 8.00mm and 4.00mm respectively, and a diameter of 1.00mm, as shown in the schematic diagram Figure 5 shown.
[0097] A concave-convex micro-texture structure is designed on the surface of the joint end 1-2, and the depth of the texture is greater than the gap width d caused by the thermal expansion and cooling sintering shrinkage of the aluminum-based ceramic material and the silicon-based ceramic material. The gap width d is estimated as follows: in the sintering process of the silicon-based ceramic green body (step S07), the final sintering temperature is 1300°C, the maximum thermal expansion rate of the aluminum-based ceramic material is ab2=0.85%, the sintering shrinkage rate is aa2=0.03%, and the silicon-based ceramic core green body is degreased and sintered to form a sintered state, and the sintering shrinkage rate is sa1=0.5%; in the high-temperature alloy pouring process, the highest temperature is 1500°C, the maximum thermal expansion rate of the aluminum-based ceramic material is ab3=1.15%, the sintering shrinkage rate is aa3=0.05%, and the sintering shrinkage rate of the silicon-based ceramic core is sa2=0.8%. The cross-sectional characteristic size of the joint end 1-2 is 1.00mm. After two thermal processes of sintering the silicon-based ceramic green body and pouring the high-temperature alloy, the gap width d can be estimated to be equal to 0.03mm. Therefore, the concave-convex micro-texture structure designed on the surface of the bonding end 1-2 is specifically set to: a sawtooth structure with a texture depth of 0.1 mm, as shown in the schematic diagram Figure 5 shown.
[0098] The remaining processes of Example 4 are the same as those of Example 1. Example 5
[0099] A ceramic core for a high-temperature alloy single crystal turbine blade is selected as the verification object, as shown in the figure Figure 6 As shown, the photocuring additive manufacturing molding part 1 is the connecting neck of the ceramic core, which is used to connect the U-shaped end and the tenon of the ceramic core; the hot injection molding part 2 is the remaining ceramic core part.
[0100] Design a digital model of the photo-curing additive manufacturing molding part 1, including a molding end 1-1 and a bonding end 1-2. Design the structure of the molding end 1-1 according to the inner cavity structure of the casting. And based on the requirements of the inner cavity size of the casting, the size of the molding end 1-1 is scaled according to the sintering shrinkage rate of the aluminum-based ceramic material. Specifically, the inner cavity of the casting requires that the connecting neck is a truncated cone structure with an R angle, the upper truncated cone diameter is 2.00 mm, the lower truncated cone diameter is 2.80 mm, the height is 4.50 mm, and R=0.80 mm; the shrinkage rate of the aluminum-based ceramic material green body sintering is aa1=0.20%, the shrinkage rate in the silicon-based ceramic green body sintering process is aa2=0.03%, and the shrinkage rate in the casting process is aa3=0.05%, thereby scaling the size of the forming end 1-1; in order to prevent the connecting end 1-2 from being exposed, the length of the forming end 1-1 is appropriately lengthened, and the structure of the aluminum-based ceramic connecting column forming end 1-1 is: the upper truncated cone diameter is 1.98 mm, the lower truncated cone diameter is 2.78 mm, the height is 4.8 mm, and R=0.80 mm, as shown in the schematic diagram. Figure 6 shown.
[0101] The structure of the joint end 1-2 is designed according to the structure of the joint of the photo-curing additive manufacturing molding part 1 (ceramic core part) and the hot injection molding part 2. Specifically: as shown in the figure Figure 6 As shown, the joint end 1-2 includes two parts, which are located at the upper end and the lower end of the connection neck. In order to ensure that the joint end 1-2 is not exposed and the thickness of the silicon-based ceramic slurry coated on all sides is greater than 0.50mm, the structure of the light-curing additive manufacturing connection column joint end 1-2 is set as follows: the upper joint end 1-2 is cylindrical, with a diameter of 1.98mm and a length of 3.00mm; the joint end 1-2 between the upper end of the cone plug and the core is cylindrical, with a diameter of 2.78mm and a length of 3.00mm, as shown in the schematic diagram Figure 6 shown.
[0102] A concave-convex micro-texture structure is designed on the surface of the joint end 1-2, and the depth of the texture is greater than the gap width d caused by the thermal expansion and cooling sintering shrinkage of the aluminum-based ceramic material and the silicon-based ceramic material. The gap width d is estimated as follows: in the sintering process of the silicon-based ceramic green body (step S07), the final sintering temperature is 1300°C, the maximum thermal expansion rate of the aluminum-based ceramic material is ab2=0.85%, the sintering shrinkage rate is aa2=0.03%, and the silicon-based ceramic core green body is degreased and sintered to form a sintered state, and the sintering shrinkage rate is sa1=0.5%; in the high-temperature alloy casting process, the highest temperature is 1500°C, the maximum thermal expansion rate of the aluminum-based ceramic material is ab3=1.15%, the sintering shrinkage rate is aa3=0.05%, and the sintering shrinkage rate of the silicon-based ceramic core is sa2=0.8%. The characteristic cross-sectional dimension of the upper joint end 1-2 is 1.98 mm, and the characteristic cross-sectional dimension of the lower joint end 1-2 is 2.78 mm. After two thermal processes of sintering the silicon-based ceramic green body and pouring the high-temperature alloy, the gap width d can be estimated to be equal to 0.07 mm and 0.10 mm respectively. Therefore, the concave-convex micro-texture structure designed on the surface of the joint end 1-2 is specifically set to: a sawtooth structure with a texture depth of 0.10 mm, as shown in the schematic diagram Figure 6 shown.
[0103] The remaining processes of Example 5 are the same as those of Example 1.
[0104] The experimental results show that: the present invention uses a light-curing additive manufacturing method to prepare a high-strength aluminum-based ceramic fine special-shaped structure, and uses a hot pressing method to prepare a silicon-based ceramic core main structure, thereby developing an aluminum-silicon-based ceramic core with good yielding properties in the main part and high impact resistance in the fine structure, solving the problem of ceramic core fracture during sintering, wax pressing and pouring, and does not introduce side effects such as high-temperature alloy recrystallization; the light-curing additive manufacturing technology can quickly prepare complex fine special-shaped ceramic structures. Compared with traditional technologies, this technology has the advantages of high dimensional accuracy, convenient structural adjustment, and short development cycle. At the same time, the present invention adjusts the matrix components of the light-curing additive manufacturing slurry, increases the fine powder content, and adds an appropriate amount of organic fiber and starch, while increasing the degree of sintering and forming an appropriate amount of pores, successfully preparing high-strength and easy-to-remove alumina-based ceramic parts, which facilitates the subsequent ceramic core removal process. In addition, this technology solves the interface separation problem caused by the mismatch between thermal expansion rate and cooling shrinkage rate of aluminum-based and silicon-based ceramic materials through the micro-interface design of the joint end 1-2 of the photocuring additive manufacturing molding part. It not only improves the sintering qualification rate of the ceramic core, but also avoids the problem of high-temperature alloy liquid infiltrating into the interface 1-2 of the joint end of the ceramic core to form excess metal during the pouring process, thereby improving the pouring qualification rate.
[0105] The above description of the disclosed embodiments enables those skilled in the art to implement or use the present invention. Various modifications to these embodiments will be apparent to those skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the present invention. Therefore, the present invention will not be limited to the embodiments shown herein, but rather to the widest scope consistent with the principles and novel features disclosed herein.
Claims
1. A method for preparing an aluminum-silicon based ceramic core, characterized in that: The following steps are involved: Step S01: according to the structural model of the ceramic core, the ceramic core is divided into a photo-curing additive manufacturing molding part (1) and a hot injection molding part (2); Step S02: designing a digital model of a light-curing additive manufacturing molding part (1), comprising a molding end (1-1) and a bonding end (1-2); the molding end (1-1) participates in forming the outer structure of the ceramic core, and the bonding end (1-2) is used to be bonded with the hot injection molding part (2); the surface of the bonding end (1-2) has a concave-convex micro-texture structure, and the texture depth is greater than the gap width caused by the mismatch between the thermal expansion rate and the sintering shrinkage rate of the aluminum-based ceramic material and the silicon-based ceramic material; The photocuring additive manufacturing molding part (1) is an aluminum-based ceramic part; The ceramic slurry of the aluminum-based ceramic part comprises: Ceramic powder 55~85wt%, photosensitive resin 10~45wt%, dispersant 1~5wt%, additive 0.1~3wt%; the ceramic powder is composed of aluminum oxide powder 95~99.9wt%, silicon oxide powder 0.1~5wt%, silicon nitride whisker 0.1~3wt%, and the sum of the contents of each component satisfies 100wt%; the aluminum oxide powder is composed of powders with particle sizes of 0.1~0.5μm, 1~2μm and 3~5μm in a mass ratio of (1.5~2.5): (6~8): 1; The silicon oxide powder is a spherical powder with a particle size of 0.3-0.8 μm; the photosensitive resin is composed of 0.4-1 wt% of an external TPO photoinitiator, 60-90 wt% of an HDDA resin, 3-15 wt% of a TMPTA resin, 3-15 wt% of a PPTTA resin, and 3-15 wt% of a PEG400DA resin, and the sum of the contents of each component satisfies 100 wt%; the dispersant is DISPERBYK-110; the additives include one or more of polyethylene fibers, multi-walled carbon nanotubes, and starch; Step S03: Printing, sintering and trimming are performed using a photo-curing additive manufacturing method to prepare a photo-curing additive manufacturing molding part (1); Step S04: designing a ceramic core mold for preparing the hot injection molding part (2), and the mold is designed with a limit slot for placing the light-curing additive manufacturing molding part (1); Step S05: placing the photocuring additive manufacturing molding part (1) into the limiting slot of the ceramic core mold, preparing the hot-pressing molding part (2) by hot-pressing method, and forming a complete ceramic core green body in which the hot-pressing molding part (2) tightly covers the joint end (1-2); the hot-pressing method comprises: using a core pressing machine to inject molten silicon-based ceramic slurry into the ceramic core mold under certain injection parameters, and after a certain holding time, the silicon-based ceramic slurry is cooled and solidified to form a complete ceramic core green body in which the hot-pressing molding part (2) covers the photocuring additive manufacturing molding part (1); the injection pressure is 4.0-7.8 MPa, the injection time is 3-8 s, the holding time is 20-50 s, the mold clamping pressure is 4.0-8.0 MPa, the mold temperature is 30-45°C, and the slurry temperature is 60-110°C; Step S06: visually inspecting to confirm that the photo-curing additive manufacturing molding part (1) and the green hot-pressing molding part (2) have no defects, and that the joint between the two has no defects; Step S07: Sintering to form a sintered ceramic core, cooling it to room temperature and then taking it out of the furnace; Step S08: Visual inspection to confirm that the ceramic core as a whole has no defects, that is, the aluminum-silicon based ceramic core is prepared.
2. The preparation method according to claim 1, characterized in that: The light-curing additive manufacturing molding part (1) in step S01 is a fine structure with a small size on the ceramic core; and the hot injection molding part (2) is the main body of the ceramic core.
3. The preparation method according to claim 1, characterized in that: The open porosity of the sintered aluminum-based ceramic part in step S07 is 5-30%, and the three-point bending strength at room temperature is not less than 300 MPa, which can be removed by soaking in high-temperature and high-pressure KOH alkali solution.
4. The preparation method according to claim 1, characterized in that: The ceramic core mold used for forming the hot injection molding part (2) in step S04 is designed with a limit slot for placing the light-curing additive manufacturing molding part (1), and a filling space for the silicon-based ceramic slurry is reserved around the joint end (1-2), so that the thickness of the silicon-based ceramic slurry is greater than 0.5 mm.
5. The preparation method according to claim 1, characterized in that: The open porosity of the sintered silicon-based ceramic component in step S07 is 20-40%, the three-point bending strength at room temperature is 10-20 MPa, and the solubility in 37% KOH boiling alkali solution is 0.08-0.15 g / min.
Citation Information
Patent Citations
Method for preparing double-wall cold ceramic core through material increase-equal material synergy
CN118163212A
Precision casting ceramic core forming die
CN209792545U